Pemicu Tax Avoidance: Financial Distress, Leverage Dan Sales Growth Studi Pada Perusahaan Sektor Basic Materials - Hidayat, Akmal; Muthohhar Rafi, Mar’ie; Kurniati, Endang (JURNAL MUTIARA AKUNTANSI, 2022)
This study aims to determine the effect of financial distress, leverage and sales growth on tax avoidance. Tax Avoidance is an act of tax avoidance carried out by taxpayers, but the actions taken do not violate applicable regulations. Financial distress, leverage and sales growth as variables that can trigger this tax avoidance. The research sample consisted of 17 companies which were determined using a purposive sampling technique with 6 years of observation, namely 2016-2021. Research data were analyzed using multiple linear regression analysis with SPSS tools. The results showed that leverage had an effect on tax avoidance, while financial distress and sales growth had no effect on tax avoidance.